2013
DOI: 10.1002/acr.21883
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Arthropathies and Joint Replacement Surgery in Patients With Genetic Hemochromatosis: A Study of 3,531 Patients and Their 11,794 First‐Degree Relatives

Abstract: Objective. Genetic hemochromatosis (GH) is an autosomal recessive disease in individuals of Northern and WesternEuropean descent. Heterozygosity for the C282Y mutation is common (6 -20%). Arthropathy is one of the few complications of GH suggested not to be associated with iron body stores; synovial iron deposition remains in iron-depleted patients. Previous studies suggest an elevated prevalence of clinical and radiographic signs of arthropathy in patients with GH, and 2 smaller studies suggest a possibly ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
3
21
0
5
Order By: Relevance
“…Among the H63D and C282Y HFE mutations and their compound heterozygotes, C282Y homozygosity in patients with SKOA resulted in significant increase in serum ferritin, confirming a previous report that C282Y mutation carriers are highly prevalent in hand OA involving metacarpophalangeal joints 2–5 and bilateral specified large joints [39]. Furthermore, a recent study has reported that patients with genetic hemochromatosis are at increased risk for arthropathies, including the need for joint replacement surgery [44]. …”
Section: Discussionsupporting
confidence: 76%
“…Among the H63D and C282Y HFE mutations and their compound heterozygotes, C282Y homozygosity in patients with SKOA resulted in significant increase in serum ferritin, confirming a previous report that C282Y mutation carriers are highly prevalent in hand OA involving metacarpophalangeal joints 2–5 and bilateral specified large joints [39]. Furthermore, a recent study has reported that patients with genetic hemochromatosis are at increased risk for arthropathies, including the need for joint replacement surgery [44]. …”
Section: Discussionsupporting
confidence: 76%
“…Interleukin-1 receptor antagonist has been shown to be effective in some patients with refractory hemochromatosis-related arthritis of the hands [49] but these data remain very limited. Natural evolution can lead to joint replacement [50]. …”
Section: Resultsmentioning
confidence: 99%
“…Bei einer Heterozygotie zeigt sich jedoch kein erhöhtes Auftreten einer Arthritis. Eine Studie von Elmberg et al [9] untersuchte hierzu 3531 HH-Patienten und 11 794 ihrer Verwandten 1. Grades, von denen angenommen wurde, dass sie heterozygot für die C282Y-Mutation sind.…”
Section: Epidemiologieunclassified
“…Es zeigten die Patienten mit HH, nicht aber ihre Verwandten, ein erhöhtes Risiko für die Entwicklung einer Arthritis und die Notwendigkeit einer Gelenkersatzoperation [9]. Träger einer heterozygoten Mutation von C282Y zeigen auch ein insgesamt erhöhtes Risiko einer klinisch relevanten Eisenüberladung [1].…”
Section: Epidemiologieunclassified